Green roofs as a technology for rainwater retention - Monteiro, Cristina (2015)
Green roofs (GR) or living roofs are a technology of roof construction with a vegetation layer on the top of a building, which has a growing dissemination. Advantages include improvement of air quality in urban areas, generation of life ecosystems in urban cities and enhancement of both energetic and acoustic efficiency of buildings. Nowadays, they arise as potential solution for the improvement of the quality of stormwater runoff for later reuse, as well as rainwater retention in the urban scenario, decreasing water runoff. In that context the major goal of the present study is to establish a GR, with autochthonous aromatic species, aiming at evaluating the characteristics of rainwater runoff after crossing a selected substrate and its retention capacity, with a view to expand the technology application. The main outcomes allowed developing a model regarding the runoff coefficients and aspects of water quality and its reuse, promoting the development of GR technology and also the improvement of the design of rainwater harvesting systems in buildings with GR.